Genetic Background as a Missing Factor in COVID-19 Severity - Alireza Tahamtan (Golestan University Of Medical Sciences, 2020)
The clinical outcome of coronavirus disease 2019 (COVID-19) varies considerably from one individual to another and severe illness occurs only in a minority of cases. Evidence supports the role of genetic background alongside host, viral and environmental factors for COVID-19 severity. It seems that host genetic background affects the balance of immune responses during SARS-CoV-2 infection, leading to different clinical courses of the disease